A Usability Evaluation of the Prototype Afrikaanse idiome-woordeboek - Ball, Liezl H.; Bothma, Theo J.D. (Lexikos, 2017)
The Afrikaanse idiome-woordeboek is a prototype e-dictionary of Afrikaans fixed expressions developed with the intention to test the functionalities of the e-dictionary. This dictionary is based on the function theory of lexicography. The e-dictionary makes use of various technologies. When digital tools are developed it is important to consider the usability of the tool. Usability evaluation was done on the Afrikaanse idiome-woordeboek to determine with what success it can be used. Discount usability methods, viz. heuristic evaluation and usability testing were used. This article reports on the findings from the usability tests which are discussed under the categories of content, information architecture, navigation, access (searching and browsing), help, customisation and the use of innovative technologies to manage data in e-dictionaries for search and display. The usability evaluation showed that the users did not always use the e-dictionary as the designers intended. Various recommendations are made to the designers of the Afrikaanse idiome-woordeboek, as well as for the design of e-dictionaries in general. Recommendations appropriate to e-dictionaries in general are made regarding usability evaluation, information architecture, searching in e-dictionaries, the data that can be included in e-dictionaries and training of users of e-dictionaries.